2020
DOI: 10.1002/agj2.20067
|View full text |Cite
|
Sign up to set email alerts
|

Strip‐till, other management strategies, and their interactive effects on corn grain and soybean seed yield

Abstract: Alleviation of cold, wet, compacted soils is of great importance for earlier planting that can lead to improved yield in short growing season environments. Strip‐till adoption in corn (Zea mays L.) has increased as a sustainable means to improve soil conditions and yield; however, the response of soybean [Glycine max (L.) Merr.] to strip‐till has been less consistent. This study aims to: (i) quantify the effect of strip‐till, row spacing (soybean only), crop rotation (corn only), fertilizer placement, and in‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Previous research with similar methodology for assessing crop canopy cover observed 1.5% lower canopy cover in soybean at the V2 growth stage from sulfentrazone applied preemergence (Arsenijevic et al 2021). Similar methodology for canopy assessment observed variation in time to reach 50% soybean canopy cover between strip-till and no-till depending on year (Potratz et al 2020). Early-season soybean canopy cover was greatest in soil management with tillage for most site-years in this study.…”
Section: Soybean Experimentssupporting
confidence: 65%
See 2 more Smart Citations
“…Previous research with similar methodology for assessing crop canopy cover observed 1.5% lower canopy cover in soybean at the V2 growth stage from sulfentrazone applied preemergence (Arsenijevic et al 2021). Similar methodology for canopy assessment observed variation in time to reach 50% soybean canopy cover between strip-till and no-till depending on year (Potratz et al 2020). Early-season soybean canopy cover was greatest in soil management with tillage for most site-years in this study.…”
Section: Soybean Experimentssupporting
confidence: 65%
“…A 0.09-m 2 quadrat was used to delineate the area used for canopy assessment. Photos of three random locations in each cover crop plot were collected with a smartphone camera and analyzed with Canopeo Software (Oklahoma State University, Division of Agricultural Sciences and Natural Resources Soil Physics program, Stillwater, OK; https://canopeoapp.com) to determine percent green canopy cover from each subsample (0% to 100%, with no green canopy at 0% and complete canopy cover at 100%) using default settings (red/green: 0.95; blue/green; 0.95, noise reduction: 100) (Arsenijevic et al 2021;Patrignani and Ochsner 2015;Potratz et al 2020;Ribeiro et al 2021). The percentage of canopy cover used for analysis was determined for each plot by calculating the average percent canopy cover from the three photos.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The camera was adjusted to square mode in order to produce a repeatable image frame with its lens centered in between the two soybean rows and perpendicular to the ground. Images were edited to remove green area from weeds and then batch analyzed for green area cover using Canopeo (Oklahoma State University, Stillwater, OK) add-on within Matlab (The Math Works, Inc., Natick, MA) (Arsenijevic et al, 2020;Potratz et al, 2020). Default Canopeo settings were used (Red/Green: 0.95, Blue/Green: 0.95, Noise reduction: 100) to maintain continuity across analyses.…”
Section: Weed and Crop Developmental Stage At Post Treatmentsmentioning
confidence: 99%
“…One of the objectives with tillage is increased spring soil warming, which can enhance corn establishment compared to no-till (Vetsch & Randall, 2002). Indeed, some previous studies comparing the effects between strip till and no-till on corn yield show increases of 4-6% with strip till in Minnesota, Wisconsin, and Illinois (Fernandez et al, 2012;Potratz et al, 2020;Vetsch & Randall, 2002). However, the yield benefit from strip till may not be universal, indicating that it may not be beneficial at every site (Viswakumar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%